EFEKTIVITAS PRA PERADILAN DALAM RANGKA PERLINDUNGAN HAK ASASI MANUSIA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG KITAB UNDANG-UNDANG HUKUM ACARA PIDANA DI WILAYAH HUKUM PENGADILAN NEGERI BENGKALIS - DANIEL SITORUS; Erdiianto '; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The dynamiics of tthe probllems tthatt ariise regardiing tthe applliicattiion of e-IDcard fiirstt so many probllems tthere are iindiicattiions iin tthe proviisiion of e-ID cardprojjectt Such corrrupttiion,, tthe second probllem iis tthe factt tthatt quiitte iintteresttiing tthatttthe refusall by some priivatte banks iin Indonesiia wiitth tthe reason tthe E-ID card KTPiis nott tthe same as tthe previious,, tthe tthiird probllem iis:: Based on tthe mandatte ofArttiiclle 63 Paragraph (3) of Law No.. 23 Year 2006 concerniing PopullattiionAdmiiniisttrattiion Ellecttroniic Identtiitty Card (e-ID) applliies nattiionalllly,, butt iin tthe caseprakttenya ttersbutt diiffiiculltt tto embodiied,, whiille tthe fourtth iissue iis ttheiimpllementtattiion of e-ID card lliifettiime.. Of tthe four iissues above autthors wriittiingtthesiis proposall iis focused on tthe probllems tthatt allll tthiird and fourtth course tthiis hasa correllattiion wiitth tthe autthor angkatt..Inii ttiittlle tthatt attttractts wriitters tto lliiftt tthe ttiittlle::"The Effecttiiveness of Polliicy Impllementtattiion Ellecttroniic- iidenttiitty Thiis sttudy aiimstto Know iimpllementtattiion-iimpllementtattiion of Ellecttroniic Identtiitty Card (e-ID) iinDiisttriictt Charmiing by Actt No.. 23 of 2006 on Popullattiion Admiiniisttrattiion and fortthe iimpllementtattiion of tthe applliicattiion Ellecttroniic- Knowiing Probllems of IdenttiittyCard (e-ID) iin Diisttriictt HandsomeBased on tthe formullattiion of tthe probllem and research objjecttiives,, tthe ttypeof research tthatt iis used by tthe autthor iis tthe llaw of sociiollogiicall research iis tthesttudy of tthe effecttiiveness of tthe llaws tthatt are applliicablle iin tthiis case I do researchon Anallysiis Scope of applliicattiion Ellecttroniic- Identtiitty Card (e-ID) Under Law LawNo.. 23 Year 2006 concerniing Popullattiion Admiiniisttrattiion iin Pekanbaru.. Theresulltts of tthiis sttudy iindiicatte Impllementtattiion of polliicy iimpllementtattiion-EllecttroniicIdenttiitty Card (e--ID) iin Diisttriictt Handsome pursuantt tto Law No.. 23 Year 2006concerniing Popullattiion Admiiniisttrattiion was lless effecttiive iitt was proven by tthemany peoplle who unttiill now have yett tto receiive E -KTP iitt proved tthere were 3858peoplle Handsome Diisttriictt resiidentts who sttiillll do nott gett an e-ID card and PolliicyIssues E-KTP iimpllementtattiion of tthe sub-diisttriictts,, namelly tthe llack of sociialliizattiionHandsome governmentt tto remotte areas,, causiing uneven iimpllementtattiion of polliicyiinformattiion as wellll as e-KTP.. Whiich iis where tthiis polliicy allso does nott meett tthegovernmentt''s ttargett when viiewed from tthe Law of tthe Republliic of Indonesiia ..Keywords:: Effffecttiiveness,, Ellecttroniic Identtiitty Card,, Legall Due